DEVELOPING AN INTEGRATED LECTURER CAREER DEVELOPMENT MODEL FOR QUALITY ASSURANCE IN EXCELLENT STUDY PROGRAMS: EVIDENCE FROM INDONESIAN ISLAMIC HIGHER EDUCATION - Devi Pramitha; Shobihatul Fitroh Noviyanti; Jamilah Jamilah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Lecturer career development has become an essential component of quality assurance in higher education, particularly in institutions striving to achieve and sustain excellent accreditation. Nevertheless, previous studies have predominantly examined lecturer career development from an individual perspective, with limited attention to its role as an integrated institutional quality assurance strategy. This study aims to develop an integrated lecturer career development model that supports quality assurance in excellent study programmes within Indonesian Islamic higher education. Employing a qualitative case study approach, the research was conducted at the Faculty of Tarbiyah and Teacher Training, UIN Maulana Malik Ibrahim Malang. Data were collected through in-depth interviews, participant observation, and document analysis involving university leaders, faculty administrators, quality assurance personnel, heads of study programmes, and lecturers. The data were analysed using an interactive qualitative analysis process consisting of data reduction, data display, thematic analysis, and conclusion drawing. The findings reveal that lecturer career development is implemented through four interconnected dimensions: KARTA (Academic Policy and Academic Transformation Roadmap), DINAMIKA (Integrative Academic Quality Navigation and Implementation Design), SIKAD (Integrated Lecturer Academic Career System), and the Integrated Lecturer Academic Career Development (IKAD) Model, which are synthesised within the Input–Process–Output–Outcome (IPOO) framework. The proposed model integrates institutional policy, academic culture, quality assurance, lecturer competency development, monitoring, evaluation, and continuous improvement into a unified institutional system that supports sustainable quality assurance and excellent study programme performance. The study contributes to higher education management literature by repositioning lecturer career development as a strategic institutional quality assurance mechanism rather than merely an individual professional development process. The IKAD Model also offers a practical framework for strengthening sustainable academic quality management within Islamic higher education institutions.